Spirituality through humanitarian fieldwork - Wan Yusoff, Wan Mazwati (IIUM Press, International Islamic University Malaysia, 2020)
Islamic spirituality is understood by many as a state of being close to Allah, affecting one's thought and actions. To many, spirituality means, among others, being absorbed in adhkar (invocation of remembrance of Allah), reading the Qur'an, performing night prayers, or following the path of sufis or mystics. It is often forgotten that spirituality can also entail giving to others, helping the needy and sharing the pains of those suffering from economic hardship. This chapter describes the experience of the author, two of her students and others who supported them in a humanitarian project they undertook. it describes a group IIUM volunteers' journey into spirituality by way of being involved in humanitarian work in conflict zones. the impetus for the involvement in the humanitarian work was derived from the Prophetic tradition that equated the believer with one who is friendly and befriended and the best of people to be those who are most beneficial to people.